AntiVIRmiR: A repository of host antiviral miRNAs and their expression along with experimentally validated viral miRNAs and their targets - Thakur, Anamika; Kumar, Manoj (Frontiers in Genetics, 2022)
miRNAs play an essential role in promoting viral infections as well as modulating the antiviral defense. Several miRNA repositories have been developed for different species, e.g., human, mouse, and plant. However, ‘VIRmiRNA’ is the only existing resource for experimentally validated viral miRNAs and their targets. We have developed a ‘AntiVIRmiR’ resource encompassing data on host/virus miRNA expression during viral infection. This resource with 22,741 entries is divided into four sub-databases viz., ‘DEmiRVIR’, ‘AntiVmiR’, ‘VIRmiRNA2’ and ‘VIRmiRTar2’. ‘DEmiRVIR’ has 10,033 differentially expressed host-viral miRNAs for 21 viruses. ‘AntiVmiR’ incorporates 1642 entries for host miRNAs showing antiviral activity for 34 viruses. Additionally, ‘VIRmiRNA2’ includes 3340 entries for experimentally validated viral miRNAs from 50 viruses along with 650 viral isomeric sequences for 14 viruses. Further, ‘VIRmiRTar2’ has 7726 experimentally validated targets for viral miRNAs against 21 viruses. Furthermore, we have also performed network analysis for three sub-databases. Interactions between up/down-regulated human miRNAs and viruses are displayed for ‘AntiVmiR’ as well as ‘DEmiRVIR’. Moreover, ‘VIRmiRTar2’ interactions are shown among different viruses, miRNAs, and their targets. We have provided browse, search, external hyperlinks, data statistics, and useful analysis tools. The database available at https://bioinfo.imtech.res.in/manojk/antivirmir would be beneficial for understanding the host-virus interactions as well as viral pathogenesis. microRNA; target; expression; antiviral; viruses; human host; network; web server